2005
DOI: 10.1002/em.20138
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the mutagenic activity of oxaliplatin and cisplatin in the Hprt gene of CHO cells

Abstract: Oxaliplatin is a platinum-derived antitumor drug that is active against cisplatin-resistant tumors and has lower overall toxicity than does cisplatin. DNA adduct formation is believed to mediate the cytotoxic activity of both compounds; however, the adducts may also be responsible for mutagenic and secondary tumorigenic activities. In this study, we have compared the mutagenicity of oxaliplatin and cisplatin in the Hprt gene of CHO-K1 cells. Both drugs produced dose-related increases in mutant frequency. For 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
38
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 52 publications
7
38
0
Order By: Relevance
“…Mismatch repair (MMR) is a post-replication repair system that corrects mispaired and unpaired bases in the duplex [75]. MMR System repairs mismatches caused by adducts that are not removed by the NER system [12]. The DNA-mismatch repair system, e.g., Msh2 corrects base -base mismatches and small loops, whereas the NER system, e.g., Rad1, removes pyrimidine dimers and other helix-distorting lesions [123].…”
Section: Recognition Of Platinatedmentioning
confidence: 99%
See 2 more Smart Citations
“…Mismatch repair (MMR) is a post-replication repair system that corrects mispaired and unpaired bases in the duplex [75]. MMR System repairs mismatches caused by adducts that are not removed by the NER system [12]. The DNA-mismatch repair system, e.g., Msh2 corrects base -base mismatches and small loops, whereas the NER system, e.g., Rad1, removes pyrimidine dimers and other helix-distorting lesions [123].…”
Section: Recognition Of Platinatedmentioning
confidence: 99%
“…The lower levels of Pt-adduct formation with oxaliplatin most likely reflect the slow dissociation rate of the oxalate ligand under physiological conditions. It has been suggested that oxaliplatin cytotoxicity might possibly result from proportionately more highly lethal lesions such as interstrand or DNA -protein cross-links [70], and from the bulkier and more hydrophobic adducts formed by oxaliplatin [12]. Recent investigations suggest that oxaliplatin displays a disproportionately greater ability to induce secondary lesions in DNA that are precursors to massive apoptosis [72].…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Although the low spontaneous mutation frequency is unlikely to generate mutations in the potential N-glycosylation sites in MRP4, oxaliplatin is quite mutagenic to mammalian cells [31] and such mutations may have arisen during the selection process. To determine whether mutation of the N-glycosylation sites in MRP4 could account for the observed glycosylation defect, we sequenced the putative glycosylation sites with primers designed using web available tools.…”
Section: Sequencing Of Putative N-glycosylation Sites Of Mrp4 and Expmentioning
confidence: 99%
“…Both cisplatin and carboplatin are effective against solid tumors such as small-cell lung, ovarian, head, and neck cancers. Oxaliplatin is often used for the treatment of primary advanced colorectal cancer and cisplatinresistant ovarian cancers (57,66). Although cisplatin and its analogs are widely used clinically, a major limitation for these compounds is the induced drug resistance.…”
Section: Pol G and Therapeutic Anticancer Agentsmentioning
confidence: 99%